Can Communication Mitigate Strategic Delays in Investment Timing? - Ayse Gül Mermer; Sander Onderstal; Joep Sonnemans (Tinbergen Institute, 2023)
In economic environments, decision-makers can strategically delay irreversible investments to learn from the actions of others. This creates free-riding incentives and can lead to socially suboptimal outcomes. We experimentally examine if and how communication mitigates this free-riding problem in an investment-timing game. In our baseline investment-timing game, participants choose when to invest in a nonrival project with uncertain returns, in groups of two or four players. The earliest investor of the group bears the costs of investment while everyone in the group benefits if the project reveals high returns. If more investors invest at the same time, they share the costs. In the communication treatment, subjects can freely communicate before choosing the investment time. We find that in groups of two players, communication increases cooperation and leads to significantly earlier investments. In groups of four players, however, communication significantly reduces delay only in the first period of interaction, but not in the aggregate over all periods
Keywords: C72; C92; D83; H41; 330; stochastic volatility; social cost of carbon; climate damage; Duffie-Epstein preference